2004
DOI: 10.1128/jcm.42.12.5558-5564.2004
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Ovine Herpesvirus 2 in Sheep Nasal Secretions: the Predominant Mode for Transmission

Abstract: Ovine herpesvirus 2 (OvHV-2), the major causative agent of malignant catarrhal fever in ruminant species worldwide, has never been propagated in vitro. Using real-time PCR, a striking, short-lived, peak of viral DNA, ranging from 10 5 to over 10 8 copies/2 g of DNA, was detected in nasal secretions from over 60.7% of adolescent sheep (n ‫؍‬ 56) at some point during the period from 6 to 9 months of age. In contrast, only about 18% of adult sheep (n ‫؍‬ 33) experienced a shedding episode during the study period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 19 publications
1
70
0
19
Order By: Relevance
“…Recognition of the short window of time when lambs are free of infection during early life under natural flock conditions (Li et al, 1998) resolved the problem and provided an opportunity to develop a programme for production of OvHV-2-free sheep . A study of OvHV-2 shedding kinetics in sheep using quantitative real-time PCR revealed that adolescent lambs between 6 and 9 months of age shed virus more frequently and intensively than adults (Li et al, 2004). These studies have made it possible to establish a source of infectious virus by collection of nasal secretions from sheep during shedding episodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the short window of time when lambs are free of infection during early life under natural flock conditions (Li et al, 1998) resolved the problem and provided an opportunity to develop a programme for production of OvHV-2-free sheep . A study of OvHV-2 shedding kinetics in sheep using quantitative real-time PCR revealed that adolescent lambs between 6 and 9 months of age shed virus more frequently and intensively than adults (Li et al, 2004). These studies have made it possible to establish a source of infectious virus by collection of nasal secretions from sheep during shedding episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that viral transmission and shedding patterns are different between OvHV-2 and AlHV-1 in their natural hosts: sheep shed the virus sporadically with a short-lived episode and new born lambs are not the source of infection (Li et al, 2004), while most newborn wildebeest calves are infected and shed virus continuously until 3-4 months of age and are the primary source of transmission (Mushi & Wafula, 1983). Recent studies revealed that the transcripts of the open reading frame (ORF) 25, a gene encoding a capsid protein, were present in virtually all tissues of cattle, bison (Cunha et al, 2007) and rabbits (Gailbreath et al, 2008) with OvHV-2-induced MCF, but not present in the tissues (spleen and lymph nodes) of rabbits with AlHV-1-induced MCF (Dewals et al, 2008), suggesting that virus lytic replication and latency are different in clinically susceptible hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Typical clinical signs include fever, inappetence, ocular and nasal discharge, diarrhea, and depression. The mode of transmission of these viruses between carriers and susceptible ruminants is uncertain, but transmission via nasal secretions from sheep to other ruminants may be the most likely route for OvHV2 (Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lambing peaks on 1 May in Lesja; thus many lambs reach an age of 6 mo during October. OvHV-2 is shed particularly by 6-9-mo-old lambs (Li et al 2004). Stress related to gathering and fencing might increase shedding.…”
Section: Malignant Catarrhal Fever (Mcf) Is a Viral Disease That Affementioning
confidence: 94%